Enhancing the Therapeutic Efficacy of Cancer Treatment With Cannabinoids - Yasmin-Karim, Sayeda; Moreau, Michele; Mueller, Romy; Sinha, Neeharika; Dabney, Raymond; Herman, Allen; Ngwa, Wilfred (Frontiers in Oncology, 2018)
Over the years, many in vitro and in vivo studies have shown the antineoplastic effects of cannabinoids, with reports advocating for investigations of combination therapy approaches that could better leverage these effects in clinical translation. This study explores the potential of combination approaches employing cannabinoids with radiotherapy (RT) or smart biomaterials towards enhancing therapeutic efficacy during treatment of pancreatic and lung cancers. In in vitro studies, clonogenic assay results showed greater effective tumor cell killing, when combining cannabinoids (CBD) and RT. Meanwhile, in vivo study results revealed major increase in survival when employing smart biomaterials for sustained delivery of cannabinoids to tumor cells. The significance of these findings, considerations for further research, and viable roadmap to clinical translation are discussed.